2009
DOI: 10.1038/onc.2009.468
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ-mediated upregulation of hepatic miR-181b promotes hepatocarcinogenesis by targeting TIMP3

Abstract: To identify microRNAs that may play a causal role in hepatocarcinogenesis, we used an animal model in which C57/BL6 mice fed choline deficient and amino acid defined (CDAA) diet develop preneoplastic lesions at 65 weeks and hepatocellular carcinomas after 84 weeks. miRNA expression profiling showed significant upregulation of miR-181b and miR-181d in the livers of mice as early as 32 weeks that persisted at preneoplastic stage. The expression of TIMP3, a tumor suppressor and a validated miR-181 target, was mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
288
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(297 citation statements)
references
References 38 publications
7
288
0
2
Order By: Relevance
“…Loss of TIMP3 expression, through loss of heterozigosity on chromosome 22q, is frequently observed in various cancers, such as secondary glioblastoma (Nakamura et al, 2005) and clear renal cell carcinomas (Masson et al, 2010). Evidence is emerging that downregulation of TIMP3 expression in tumors can be achieved also through deregulation of microRNAs, as TIMP3 is a target of several microRNAs upregulated in human tumors such as miR21, miR181b, miR221 and 222 (Gabriely et al, 2008;Garofalo et al, 2009;Wang et al, 2010). The tumor-suppressor role of TIMP3 is also documented by a large body of data showing its capability to inhibit growth, invasion and metastasis of several cancers (Anand-Apte et al, 1996;Qi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Loss of TIMP3 expression, through loss of heterozigosity on chromosome 22q, is frequently observed in various cancers, such as secondary glioblastoma (Nakamura et al, 2005) and clear renal cell carcinomas (Masson et al, 2010). Evidence is emerging that downregulation of TIMP3 expression in tumors can be achieved also through deregulation of microRNAs, as TIMP3 is a target of several microRNAs upregulated in human tumors such as miR21, miR181b, miR221 and 222 (Gabriely et al, 2008;Garofalo et al, 2009;Wang et al, 2010). The tumor-suppressor role of TIMP3 is also documented by a large body of data showing its capability to inhibit growth, invasion and metastasis of several cancers (Anand-Apte et al, 1996;Qi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is considerable interest in understanding factors regulating TIMP-3 levels, and it has been shown that transcription of TIMP-3 can be increased by the histone deacetylase SirT1 (10) and growth factors such as TGF␤ (11) and oncostatin M (12) and reduced by promoter methylation (13). Translation of TIMP-3 can be reduced by miR-21 (14), miR-221 and miR-222 (15), miR-181b (16), and miR-206 (17).…”
Section: Tissue Inhibitor Of Metalloproteinases-3 (Timp-3) Plays a Kementioning
confidence: 99%
“…It is important to note that the effects of miR-181b in chemoresistance vary according to different tumor microenvironments. In hepatocellular carcinoma (HCC) cells, miR-181b enhances resistance to the anticancer drug doxorubicin (10). A markedly miR-181b increases drug sensitivity in acute myeloid leukemia via targeting HMGB1 and Mcl-1 enhanced expression of miR-181b was also shown in more aggressive breast cancers and chemotherapy-resistant breast cancer cells, and knockdown of miR-181b can be used to render breast tumors more responsive to tamoxifen (11,12).…”
Section: Introductionmentioning
confidence: 99%